2015
DOI: 10.1111/jpi.12249
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide metabolism regulates autophagy and apoptotic cell death induced by melatonin in liver cancer cells

Abstract: Autophagy is a process that maintains homeostasis during stress, although it also contributes to cell death under specific contexts. Ceramides have emerged as important effectors in the regulation of autophagy, mediating the crosstalk with apoptosis. Melatonin induces apoptosis of cancer cells; however, its role in autophagy and ceramide metabolism has yet to be clearly elucidated. This study was aimed to evaluate the effect of melatonin administration on autophagy and ceramide metabolism and its possible link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 81 publications
2
98
1
Order By: Relevance
“…The identification of molecular pathways accounting for the protective effect of melatonin in liver diseases would aid in finding novel therapeutic options to prevent liver injury. It was shown recently that ceramides and ER stress via JNK phosphorylation have a major role in the control of autophagy and apoptosis in hepatocarcinoma cells treated with melatonin; this indicates that sphingolipids could be an important link between the UPR and the mechanisms that control cell death and survival .…”
Section: Melatonin and Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of molecular pathways accounting for the protective effect of melatonin in liver diseases would aid in finding novel therapeutic options to prevent liver injury. It was shown recently that ceramides and ER stress via JNK phosphorylation have a major role in the control of autophagy and apoptosis in hepatocarcinoma cells treated with melatonin; this indicates that sphingolipids could be an important link between the UPR and the mechanisms that control cell death and survival .…”
Section: Melatonin and Liver Diseasesmentioning
confidence: 99%
“…The contents of these organelles are degraded by lysosomal enzymes . In some cell types, such as tumor cells, autophagy plays a dual role favouring cell adaptation to different stresses (hypoxia or starvation) and survival or the induction of cell death in other situations when protein and organelle turnover overwhelms the capacity of the cell . Although the crosstalk between autophagy and apoptosis is still not clearly defined, a relationship has been established due to the interaction of different autophagy‐ and apoptosis‐related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin exerts anti-apoptotic effects in normal cells exposed to toxic agents or metabolic injury. However, melatonin usually has the opposite effect on cancer cells and induces apoptosis in a wide range of different tumors (e.g., breast, prostate, cervix, liver, colon, pancreas, kidney, neuro) [18, 20, 24, 25, 28, 7578]; thus, the induction of apoptosis of cancer cells (but not of normal cells) is one of the mechanisms by which melatonin limits tumor growth [61, 7988]. This specifically relates to lung cancer given that melatonin treatment dose- and time- dependent decreased the viability of human A549 and PC9 lung adenocarcinoma cells, and increased their apoptotic index.…”
Section: Effect Of Melatonin On Nsclc Cell Apoptosismentioning
confidence: 99%
“…As a potent free radical scavenger and antioxidant, melatonin has the capacity to scavenge up to 10 reactive oxygen species (ROS) via the cascade reaction means, which distinguishes melatonin from the classic antioxidants that scavenge only one or less ROS [1113]. Additionally, numerous publications have reported that melatonin inhibits the growth of a variety of cancers: lung [5, 14, 15], breast [1620], prostate [2124], liver [25, 26], colon [27, 28], etc. The oncostatic mechanisms of melatonin are related to several hallmarks of cancer, including anti-proliferation [14], induction of apoptosis [5, 14, 15], inhibition of invasion and metastasis [29, 30], anti-angiogenesis [16, 31], and enhancement of immunomodulation [32] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Pro-death autophagy is the most recent anti-tumour activity to be described as a prosurvival mechanism, and studies have suggested that autophagy can promote cell death within different cellular contexts. Ordonez et al reported that melatonin induced autophagy in HepG2 cells, which was mediated by ER stress and JNK activation [64]. Bcl-2 and Bcl-xL, which are involved in cell apoptosis, also play crucial roles in autophagy [65], and inhibition of Bcl-2 and Bcl-xL expression and enhancement of JNK1/2 signalling may result in the activation of Beclin-1-mediated autophagy [66].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Suppresmentioning
confidence: 99%